PENGARUH MOTIVASI INTRINSIK, KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI PADA KANTOR PEMERINTAHAN DESA UBUNG KAJA - Ni Kadek Shintya Rahayu; I Wayan Sujana; Ni Nyoman Ari Novarini (EMAS, 2022)
Human resources are one of the most important factors in an organization. Human resources must be managed properly in order to increase the effectiveness and efficiency of the organization so that it is able to support the achievement of organizational goals. Organizations in an effective and efficient institution have various dimensions to support operational performance, including their human resources. This human resource factor is the main thing in the organization of an institution. The sample in this study were all employees at the Ubung Kaja village government office as many as 36 people. The sampling technique used is the saturated sampling method.Data collection techniques used in this study were observation, interviews and questionnaires. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation analysis, analysis of determination (R2), f test and t test.The results show that intrinsic motivation, individual characteristics, and job characteristics have a positive and significant effect on employee performance, so it is better for leaders to provide better job skills training in order to increase the ability of each individual employee, provide a comfortable work environment and give appreciation to outstanding employees to spur the improvement of other employees' work, so as to improve employee performance at the Ubung Kaja Village Government Office.